ANALYSIS OF THE IMPACT OF PROMOTIONS, PRICES, AND PRODUCT INNOVATIONS FROM BUY DECISIONS AT PT. CAPELLA DINAMIC NUSANTARA - Justin Alexander; Nurmaidah Ginting; Lola Rossa Br. Hutauruk; Gabrio Agata Kaban; Emma Novirsari (Mount Hope Economic Global Journal, 2024)
Capella Dinamik Nusantara is a company operating in the automotive sector, particularly in the distribution and sale of motorcycles and their spare parts. As an official dealer, this company collaborates with various well-known brands to provide quality products to consumers. The purpose of this journal is to analyze the influence of promotion, price, and product innovation on purchase decisions at PT. Capella Dinamik Nusantara. The population of this study consists of the consumers of PT. Capella Dinamik Nusantara. The sample for this research includes 100 consumers from PT. Capella Dinamik Nusantara. Data collection was conducted through a questionnaire distributed via Google Forms. The results of data analysis using SEM-PLS statistical software indicate that the variables of promotion, price, and product innovation have a partial and simultaneous influence, with F-test values >0.062, T- test values with a T-statistic >1.96, and P-value <0.05.